Breach Of Contract In Focus: Legal Analysis Of Debt Transfer, Property Rights, And Contractual Obligations - Gunawan, Anneke Catlynne; Gunadi, Chaterine Grace; Indrakusuma, Jason; Emmanuel Stutanto, Theodore Francisco; Tanaya, Velliana; Nugraha, Dewi (UNIVERSITAS PAKUAN, 2025)
AbstrakThis article explores the legal framework surrounding breach of contract in Indonesian civil law, with particular focus on debt transfer, property rights, and the enforcement of contractual obligations. By analyzing two recent court decisions—a Supreme Court ruling and a High Court judgment from Surabaya—the study examines how Indonesian judges interpret and apply the principles of contract law in practice. The first case highlights the legal implications of unfulfilled obligations and delayed property settlement, while the second illustrates the procedural and substantive challenges in resolving disputes involving transferred debts and overlapping property claims. The discussion reveals how courts evaluate evidence, assess good faith, and determine liability. The article argues for clearer standards in interpreting contract breaches and a more consistent application of the rules governing debt transfer and secured property rights. These findings contribute to a deeper understanding of judicial tendencies and their implications for legal certainty and contract enforcement in Indonesia. Keywords: Breach of contract, ebt transfer, Property rights, Contractual obligations, Indonesian civil law.